Understanding Strategies of Anti-Nuclear Movement: A Study of ICAN [Memahami Strategi Gerakan Anti-Nuklir:Sebuah Studi Tentang ICAN - Mutti Anggitta (Sekretariat Jenderal DPR RI, 2021)
This article argues that the most unique characteristic of the ICAN’s activism is its transnational scope, which was made possible by the use of eight strategies by the organization including geostrategic headquarters, internet and technology, government relations, NGOs connection, celebrity spotlight, perfect timing, creativity, and responsiveness. In evaluating the argument, this article provides evidence by employing process-tracing methods and conducting archival analysis to closely examine the historical timeline of important events or moments surrounding the ICAN’s activism since its inception in 2007 to the adoption of the Treaty on the Prohibition of Nuclear Weapons in 2017. This article first provides a literature review on social movements against nuclear weapons to provide some background. It then describes how the eight strategies are employed by the ICAN as they are reflected in its transnationalactivism. It finally notes the five key milestones that are achieved by the organization.AbstrakArtikel ini berargumen bahwa karakteristik paling unik dari aktivisme ICAN adalah jangkauannya yang bersifat transnasional, yang dicapai berkat penggunaan delapan strategi mencakup letak kantor pusat yang strategis, internet dan teknologi, hubungan dengan pemerintah, jejaring LSM, sorotan selebriti, pemilihan waktu yang tepat, kreativitas, dan kemampuan merespon. Dalam mengevaluasi argumen tersebut, artikel ini memaparkan data dengan menggunakan metode process tracing dan melakukan analisis arsip untuk memeriksa secara detail peristiwa-peristiwa penting seputar aktivisme ICAN sejak didirikan pada 2007 hingga diadopsinya Perjanjian Pelarangan Senjata Nuklir pada 2017. Artikel ini menyediakan tinjauan pustaka tentang gerakan sosial melawan senjata nuklir untuk menjelaskan latar belakang isu ini. Kemudian artikel ini menjelaskan bagaimana delapan strategi tersebut digunakan oleh ICAN, sebagaimana tercermin dalam aktivisme transnasionalnya. Di akhir, artikel ini mengidentifikasi lima pencapaian utama yang diraih oleh ICAN.